Improvement of Wind Power Assessment in Complex Terrain: The Case of COSMO-1 in the Swiss Alps - Kruyt, Bert; Dujardin, Jérôme; Lehning, Michael (Frontiers in Energy Research, 2018)
This work contains a series of calculations that explore the wind power potential in Switzerland using the Numerical Weather Prediction model COSMO-1. The model’s performance was validated in complex terrain by comparing the modelled hourly wind speed to weather stations across Switzerland’s mountains during a two year period. For wind-exposed stations, mean RMSE was found to be 2.87 m/s, mean MBE 0.03 m/s and mean correlation 0.51. For the wind-sheltered stations, model performance is slightly worse. We use the modelled wind speeds to calculate potential power production, and find capacity factors up to 0.42. With the modelled power time series, we show that in a hypothetical fully renewable Swiss power system, turbine siting can have a significant effect on imports, which may attain values from 6 TWh/a to 13.3 TWh/a. Most importantly, the lowest import values are found for high wind power scenarios. When selecting locations with high capacity factors only (from random subsets of available locations), influence on import becomes small. An annual wind energy target of 6 TWh can be reached with as little as 1914 MW of turbine capacity, but this requires turbines to be built at relatively high elevations (mean turbine elevation 2967 above sea level). The lower the mean elevation of the wind turbines, the more capacity is required to reach the same production target. Furthermore, when restricting potential installations to locations deemed suited by the Swiss federal government (as laid out in the policy document ‘Konzept Windenergie Schweiz’), the capacity required to produce 6 TWh annually was found to be 2508 MW.